Study on the reaction pathways of steam methane reforming for H2 production. (15th September 2020) - Cai, Lei; He, Tianzhi; Xiang, Yanlei; Guan, Yanwen
Abstract: Steam methane reforming is a common commercial technology for practical H2 production. The steam methane reforming process is numerically studied in this work. The key elementary reactions and intermediate species are analyzed to reveal H2 reaction pathways. Influences of temperature, pressure and S/C (the ratio of steam to carbon) on the H2 reaction pathways are investigated. The results demonstrate that the intermediate species, CH3, C2 H6 and CH3 OH play an important role in H2 yield. When temperature increases from 600 °C to 1000 °C under 3 MPa and S/C = 3, mole fraction of H2 at outlet rises from 44.91% to 50.21% and the energy efficiency of the reforming process rises from 64.81% to 80.63%. Pathways of CH4 →H2 and CH3 OH→CH2 OH→CH2 O→H2 are strengthened. With pressure rising from 2 MPa to 3 MPa under 600 °C and S/C = 3, mole fraction of H2 and the energy efficiency vary from 40.79% to 44.91% and 61.29%–64.81% respectively. Pathways of C2 H6 →C2 H5 →H2 and CH3 OH→H2 make more contributions to the yield of H2 . When S/C rises from 3 to 6 under 600 °C and 3 MPa, dry mole fraction of H2 and the energy efficiency change from 71.52% to 75.85% and 64.81%–89.07% respectively. CH3 OH→H2, CH3 OH→CH2 OH→CH2 O→H2 and CH3 OH→CH2 OH→CH2 O→HCO→H2 are significantly enhanced by the rising S/C. Highlights: The steam methane reforming for H2 production is numerically studied in detail. Key elementary reactions and important intermediate species are determined. Detailed reaction pathways of H2 production in steam methane reforming are proposed. Effect mechanisms of temperature, pressure and S/C on H2 production are revealed.